Regional differences in multidimensional aspects of health: findings from the MRC cognitive function and ageing study - Brayne Carol; Miller Laura L; Matthews Fiona E; Jagger Carol (BMC, 2006)
Abstract Background Differences in mortality and health experience across regions are well recognised and UK government policy aims to address this inequality. Methods combining life expectancy and health have concentrated on specific areas, such as self-perceived health and dementia. Few have looked within country or across different areas of health. Self-perceived health, self-perceived functional impairment and cognitive impairment are linked closely to survival, as well as quality of life. This paper aims to describe regional differences in healthy life expectancy using a variety of states of health and wellbeing within the MRC Cognitive Function and Ageing Study (MRC CFAS). Methods MRC CFAS is a population based study of health in 13,009 individuals aged 65 years and above in five centres using identical study methodology. The interviews included self-perceived health and measures of functional and cognitive impairment. Sullivan's method was used to combine prevalence rates for cognitive and functional impairment and life expectancy to produce expectation of life in various health states. Results The prevalence of both cognitive and functional impairment increases with age and was higher in women than men, with marked centre variation in functional impairment (Newcastle and Gwynedd highest impairment). Newcastle had the shortest life expectancy of all the sites, Cambridgeshire and Oxford the longest. Centre differences in self-perceived health tended to mimic differences in life expectancy but this did not hold for cognitive or functional impairment. Conclusion Self-perceived health does not show marked variation with age or sex, but does across centre even after adjustment for impairment burden. There is considerable centre variation in self-reported functional impairment but not cognitive impairment. Only variation in self-perceived health relates to the ranking of life expectancy. These data confirm that quite considerable differences in life experience exist across regions of the UK beyond basic life expectancy.